Improvement of catalytic stability and carbon resistance in the process of CO2 reforming of methane by CoAl and CoFe hydrotalcite-derived catalysts. (26th April 2018) - Aider, N.; Touahra, F.; Bali, F.; Djebarri, B.; Lerari, D.; Bachari, K.; Halliche, D.
Abstract: The CoAl-LDH and CoFe-LDH hydrotalcite-like compounds (LDH = Layered Double Hydroxides named also hydrotalcite), were successfully synthesized following co-precipitation method at pH = 12. A several characterization techniques including TGA, ICP, XRD, N2 adsorption and desorption, H2 -TPR, O2 -TPO, SEM-EDX and TEM, were utilized to determine the structure function relationship for the obtained catalysts. These catalysts were evaluated in CO2 reforming of methane under continuous flow with CH4 /CO2 ration equal to 1, at atmospheric pressure and a temperature range between 400 and 700 °C. The iron addition to the cobalt showed improved resistance to coke deposition while a slight decrease in methane conversion was observed compared to CoAlcal -R catalyst (cal = after calcination and R = after reduction) derived from CoAl-LDH precursor. Highlights: CoAl and CoFe catalysts were prepared from hydrotalcite by co-precipitation method. Calcination and reduction of solids afforded nanoparticle Co 0 with high surface area. Iron addition to the cobalt showed improved resistance to coke deposition. The low activity of the CoFe catalyst is correlated with the re-oxidation of the Co 0 .